2017
DOI: 10.1024/0301-1526/a000660
|View full text |Cite
|
Sign up to set email alerts
|

Auricular vagal nerve stimulation in peripheral arterial disease patients

Abstract: Summary:Background: Auricular nerve stimulation has been proven effective in different diseases. We investigated if a conservative therapeutic alternative for claudication in peripheral arterial occlusive disease (PAD) via electroacupuncture of the outer ear can be established. Patients and methods: In this prospective, double-blinded trial an ear acupuncture using an electroacupuncture device was carried out in 40 PAD patients in Fontaine stage IIb. Twenty patients were randomized to the verum group using a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…aVNS was also reported to increase the velocity of cerebral blood flow in the supratrochlear artery and the middle cerebral artery in single patients (Széles and Litscher, 2004). aVNS decreased the carotid-femoral pulse wave velocity, as shown by a clinical trial in Hackl et al (2017).…”
Section: Vagus Nerve Stimulation – From Biophysics To Animal and To Hmentioning
confidence: 77%
See 1 more Smart Citation
“…aVNS was also reported to increase the velocity of cerebral blood flow in the supratrochlear artery and the middle cerebral artery in single patients (Széles and Litscher, 2004). aVNS decreased the carotid-femoral pulse wave velocity, as shown by a clinical trial in Hackl et al (2017).…”
Section: Vagus Nerve Stimulation – From Biophysics To Animal and To Hmentioning
confidence: 77%
“…Auricular vagus nerve stimulation significantly improved symptoms in peripheral arterial occlusive disease through significantly increased pain-free walking distance, as shown in a case series in Payrits et al (2011). However, a clinical trial in Hackl et al (2017) has shown a significant increase in the initial walking distance in both verum and control groups, whereas the total scope of the Walking Impairment Questionnaire significantly improved only in the verum group.…”
Section: Vagus Nerve Stimulation – From Biophysics To Animal and To Hmentioning
confidence: 82%
“…aVNS therapeutic effects (Kaniusas et al, 2019a , b ) in inflammation, respiratory dysfunction and cardiovascular diseases include reduction of pro-inflammatory cytokines (Tracey, 2007 ; Stavrakis et al, 2015 ), decrease of inflammation level in chronic inflammatory processes like rheumatoid arthritis, postoperative ileus, inflammatory bowel disease (Crohn's disease, ulcerative colitis), systemic inflammation and attenuation of the acute postsurgical inflammatory response after lung lobectomy (Barone et al, 2007 ; Bernateck et al, 2008 ; Chakravarthy et al, 2015 ; Kox et al, 2015 ; Marshall et al, 2015 ; Bonaz et al, 2016 ; Koopman et al, 2016 ; Kwan et al, 2016 ; French et al, 2017 ; Hoover, 2017 ; Salama et al, 2017 ). aVNS resulted in an increase of the middle cerebral and supratrochlear artery blood flow velocity in human subjects (Széles and Litscher, 2004 ) and a decrease of the velocity of the carotid-femoral flow (Hackl et al, 2017 ). aVNS diminishes systolic blood pressure in subjects with coronary artery diseases as well as in subjects with dysfunctions of glucose metabolism (Zamotrinsky et al, 2001 ; Huang et al, 2014 ; Stavrakis et al, 2015 ) it suppresses atrial fibrillation in patients with paroxysmal atrial fibrillation (Afanasiev et al, 2016 ) and reliefs anginal symptoms in coronary artery disease patients (Zamotrinsky et al, 1997 ).…”
Section: Resultsmentioning
confidence: 99%
“…The ANS ensures homeostasis by regulating the blood circulation (dilation and constriction of blood vessels), the anti-inflammatory response, the function of internal organs and controls the heart rate (HR) and heart rate variability (HRV) [2]. The electrical stimulation of auricular vagal afferents initiates an efferent modulation, resulting in physiological changes that can be used in the treatment of cardiovascular and inflammatory diseases [3][4][5], neurological conditions [6,7] and pain [8]. Compared to surgical procedures and medicamentous treatment, pVNS is a minimally-invasive technique that comes with low risk factors and side-effects and a high overall treatment satisfaction [9].…”
Section: Introductionmentioning
confidence: 99%